Broadband self-powered photoelectrochemical photodetector based on Te/Se heterostructure nanocomposites. (June 2022) - Wang, Yaling; Zhao, Fulai; Wang, Yu; Zhang, Yichao; Shen, Yongtao; Feng, Yiyu; Feng, Wei
Abstract: Van der Waals (vdW) heterojunctions formed from different nanomaterials not only have the characteristics of each material but also exhibit novel physical properties due to the combination of them. In this work, we report on the facile synthesis of Te/Se heterostructure nanocomposites, and their application as a photosensitive material for photoelectrochemical (PEC)-type photodetectors. The Te/Se-based PEC-type photodetectors are found to achieve excellent photodetection performance and have a broad optical response spectrum that covers the ultraviolet (365 nm) to near-infrared (980 nm) regions. With 1.0 M KOH as the electrolyte, the Te/Se-based PEC-type photodetectors exhibit a photoresponsivity of 4.04 μA W −1, a specific detectivity of 1.6 × 10 7 Jones, and a fast response time of less than 0.2 s under 365 nm illumination at 0 V, indicating excellent self-powered capability. Additionally, under an applied bias potential of 0.6 V, the photodetectors exhibit a high photoresponsivity of up to 83.19 μA W −1 and a specific detectivity of 3.3 × 10 8 Jones. Moreover, the Te/Se-based PEC-type photodetectors show good cycle stability after loop running for 1500 s. Graphical abstract: Image 1 Highlights: Novel Te/Se heterostructure nanocomposites (Te/Se NCs) were synthesised by a facile two-step process. Te/Se NCs exhibits preferable photoresponsivity. Te/Se NCs-based PEC photodetectors exhibit a broadband photoresponse region from ultraviolet to near-infrared. Te/Se NCs shows promising potential for fast-response self-powered photodetectors.